Chapter 19 Ageism and Anti-Ageism in the Legal System: A Review of Key Themes (2018)
Social phenomena that have an impact on European societies, such as ageism, can be explored and better understood by looking at the ways in which the law incorporates, supports, or attempts to oppose them. This chapter – which is the first of three different contributions in this book concerned with the legal aspects of ageism in Europe – provides a descriptive overview of the inter-connections between European law and ageing. By describing and summarizing selected elements of, EU human rights and discrimination law, the chapter makes a contribution towards a better understanding of the relationships between law, ageing, and ageism.